Spatial arrangement of the animal male germ cell genome: III. A new experimental evidences in support of the Megarosette-loop model of spatial organization of chromosomes in Drosophila sperm genome - Alexandrov, Igor; Alexandrova, Margarita V.; Stepanenko, Victor A.; Korablinova, Svetlana V.; Korovina, Larisa N.; Stetsenko, Stanislav G. (İstanbul Kültür Üniversitesi, 2008)
The data on the non-random pattern of induction of the black (b) inversions in autosome 2 after action of γ-rays of 60Co or 0.85 MeV fission neutrons on Drosophila mature spermatozoa were described and 2D model of spatial arrangement of this autosome in sperm nucleus at the time of irradiation based on these data was presented. The main features of this model found to be entirely consistent with the chromosome macroarchitecture proposed earlier on the basis of data for the vestigial (vg) inversions at the same autosome. A general 2D and 3D models for the specific megarosette-loop structure of autosome in question with both sets of the inversion data were constructed validity of which was independently confirmed by the induction patterns of inversions not associated with the locus-specific mutations under study. It is stated that there are all reasons to believe that all other chromosomes in sperm genome have the same spatial macroarchitecture as the most compact and suitable one to pass on the genetic information from one generation to another. It is particularly emphasized that large-scale chromosome geometry proposed is fundamentally unlike Rabl’s configuration of interphase chromosomes in animal somatic cells. The conversion of Rabl’s configuration to megarosetteloop structure is presumed to keep pace with protein remodeling of chromatin in late spermiogenesis.
Keywords: Radiation; inversions; 2D/3D models of haploid chromosome; sperm genome; Drosophila; radyasyon; inversiyonlar; Haploid kromozomun 2D/3D modelleri; sperm genom